Carbon-sequestering and oxygen producing functions of urban forests of Kyiv city and pre-urban forests of Stockholm city - Lakyda, Ivan (2011)
Interest to carbon-sequestering and oxygen-producing functions of forest has risen considerably during last decades. Abovementioned functions of forest ecosystems acquire special significance in pre-urban and urban forests. These forests perform not only stabilizing and protective functions, but also are a renewable resource. Due to rapid development of modern technologies (bioenergy), the latter named feature becomes more and more important. However, currently there is practically no one scientifically based assessment of abovementioned functions of pre-urban forests, especially in comparison with other regions and countries. The main aim of this study was to assess and quantify carbon sequestration and production of oxygen of selected parts of urban forests of Kyiv city and pre-urban forests of Stockholm city, and to compare the results. Within this study, techniques developed by P. Lakyda (computation of phytomass and sequestered carbon) and N. Tshesnokov and V. Dolgosheev (estimation of oxygen productivity of forests) were applied. Authors have encountered numerous “compatibility problems” with the technique used and the initial datasets. Nevertheless, majority of the problems were solved successfully, thus enabling accomplishment of the main aim. This research is important as a test of compatibility of different methodologies and datasets, and provides quantitative estimation of carbon-sequestering and oxygen-producing functions of the studied forests.